Literature Review: Nurses’ Caring Behavior in Emergency Situations - Nur Habibah; Viegas, Efigenia; Indra Samban, Ian; Devi Oktarina, Natalia (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
<header class="x1n2onr6 x9f619 x78zum5 x6s0dn4 xh8yej3 x7j6532 x1j6awrg x1te75w5 x1iygr5g x4eaejv xcock1l xl9llhp x1qj619r x1r9ni5o xb1pvdl x42zw1d x889kno x1a8lsjc xf7dkkf xv54qhq x1s928wv x1h1zc6f x1280gxy xstzfhl x11iowje" data-testid="conversation-header"> Emergency services require nurses to have high competence and to demonstrate caring behavior in delivering fast, accurate, and holistic care. Caring behavior is an important indicator of the quality of nursing services; however, various studies indicate that its implementation is still not optimal. This study aims to identify the factors influencing nurses’ caring behavior in emergency situations using a systematic literature review method.The literature search was conducted through Google Scholar and PubMed with inclusion criteria including articles published between 2020 and 2026, written in Indonesian or English, involving nurse subjects, and available in full-text form. A total of 10 articles were analyzed in this study. The results show that nurses’ caring behavior is influenced by individual factors (personality), psychological factors (work motivation), and organizational factors (workload and rewards). Workload is identified as the most dominant factor, where high workload can reduce the quality of caring behavior. Work motivation is positively associated with caring behavior, while demographic characteristics do not show a significant influence. In conclusion, nurses’ caring behavior is influenced by interrelated factors, particularly workload and motivation. Therefore, optimal workload management and enhanced motivation through organizational support are necessary to improve the quality of nursing care in emergency units. </header>